High Grade Dermatologic Adverse Events Associated With Immune Checkpoint Blockade for Cancer - Kuo, Alyce M.; Markova, Alina (Frontiers in Medicine, 2022)
Immune checkpoint blockade (ICB) improves survival in many types of cancers including melanoma, non-small cell lung, renal cell, breast, and cervical cancers. However, many of these therapies are also associated with high grade dermatologic adverse events (DAEs), including Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS/TEN), SJS/TEN-like reactions, high grade maculopapular and psoriasiform rashes, autoimmune bullous eruptions, drug reaction with eosinophilia and systemic symptoms (DRESS), and acute generalized exanthematous pustulosis (AGEP), which may limit their tolerability and use. It is important to properly identify and treat DAEs to ICB because these DAEs may be associated with positive anti-tumor response and patients may have limited options for alternative anti-cancer therapeutics. In this review, we describe high grade DAEs to increasingly used ICB agents, which target CTLA-4 and PD-1 or its ligand, PD-L1 and enable the immune system to target cancer cells. We further differentiate life-threatening adverse reactions from mimickers and report cases of serious DAEs which have been recorded in association with ICB through the FDA Adverse Events Reporting System (FAERS), which is an archive of adverse events associated with various drugs and therapeutic biologic products reported voluntarily by consumers and healthcare professionals as well as mandatorily by manufacturers. Lastly, we summarize management recommendations for these adverse events and discuss knowledge and evidence gaps in this area.